Derivatives of any order of the hypergeometric function pFq(a1, ..., ap; b1, ..., bq; z) with respect to the parameters ai and bi - Ancarani, L.U. (2010)
The derivatives of any order of the general hypergeometric function pFq(a1.....ap; b1.....bq;z) with respect to the parameters a; or bj are expressed, in compact form, in terms of generalizations of multivariable Kampe de Feriet functions. To achieve this, use is made of Babister's solution to nonhomogeneous differential equations for pFq(a1.....ap; b1.....bq;z). An application to Hahn polynomials, which are 3F2 functions, is given as an illustration.